Oral dosing of chemical indicators for in vivo monitoring of Ca2+ dynamics in insect muscle - Ferdinandus (2015)
This paper proposes a remarkably facile staining protocol to visually investigate dynamic physiological events in insect tissues. We attempted to monitor Ca2+ dynamics during contraction of electrically stimulated living muscle. Advances in circuit miniaturization and insect neuromuscular physiology have enabled the hybridization of living insects and man-made electronic components, such as microcomputers, the result of which has been often referred as a Living Machine, Biohybrid, or Cyborg Insect. In order for Cyborg Insects to be of practical use, electrical stimulation parameters need to be optimized to induce desired muscle response (motor action) and minimize the damage in the muscle due to the electrical stimuli. Staining tissues and organs as well as measuring the dynamics of chemicals of interest in muscle should be conducted to quantitatively and systematically evaluate the effect of various stimulation parameters on the muscle response. However, existing staining processes require invasive surgery and/or arduous procedures using genetically encoded sensors. In this study, we developed a non-invasive and remarkably facile method for staining, in which chemical indicators can be orally administered (oral dosing). A chemical Ca2+ indicator was orally introduced into an insect of interest via food containing the chemical indicator and the indicator diffused from the insect digestion system to the target muscle tissue. We found that there was a positive relationship between the fluorescence intensity of the indicator and the frequency of electrical stimulation which indicates the orally dosed indicator successfully monitored Ca2+ dynamics in the muscle tissue. This oral dosing method has a potential to globally stain tissues including neurons, and investigating various physiological events in insects.